Tapping farmers' knowledge of crop protection - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1990)
Training courses, seminars and farmer group follow-up activities on the subject of natural crop protection, organized in Cameroon since 1-988, have proved that farmers' experiences are a rich source of ideas for those involved in adaptive research....